2007
DOI: 10.2527/jas.2006-524
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of porcine satellite cells to adipoblasts with ciglitizone1

Abstract: Ciglitizone, a class of thiazolidinediones, acts as a potent activator of the adipose differentiation program in established preadipose cell lines. Thiazolidinediones have also been investigated in diabetic patients and have been reported to act as peroxisome proliferator-activated receptor-gamma ligands. Intramuscular adipogenesis or marbling through transdifferentiation of satellite cells in cattle was successfully conducted earlier. In this report, the effects of ciglitizone on the differentiation pathway o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 39 publications
5
54
0
Order By: Relevance
“…Another complexity in the regulation of intramuscular adipocyte development is added by the possible existence of interconversion of muscle satellite cells into adipocytes as shown in vitro (Kook et al, 2006;Singh et al, 2007;for review, see Chung and Johnson, 2008). It remains, however, to be determined whether this phenomenon also exists in vivo, and may account for fat infiltration into muscles observed following denervation (Dulor et al, 1998) or sarcopenia (for review, see Pahor and Kritchevsky, 1998).…”
Section: How Might Marbling Begin?mentioning
confidence: 99%
“…Another complexity in the regulation of intramuscular adipocyte development is added by the possible existence of interconversion of muscle satellite cells into adipocytes as shown in vitro (Kook et al, 2006;Singh et al, 2007;for review, see Chung and Johnson, 2008). It remains, however, to be determined whether this phenomenon also exists in vivo, and may account for fat infiltration into muscles observed following denervation (Dulor et al, 1998) or sarcopenia (for review, see Pahor and Kritchevsky, 1998).…”
Section: How Might Marbling Begin?mentioning
confidence: 99%
“…Similarly, MSCs respond to high concentrations of the same transcription factors. However, these factors appear to inhibit myogenic differentiation Campos, Duarte, Guimarães, Verardo, Wei, Du, Jiang, Bergen, Fernyhough-Culver, Albrecht and Dodson stimulating adipogenesis and also appears to inhibit myogenic differentiation, while ensuring adipogenic differentiation (Teboul et al, 1995;Taylor-Jones et al, 2002;Singh et al, 2007;. Considering this, the study of adipogenesis and its effects on the accumulation of IMF can be used not only to understand fat deposition in livestock, but also for a better comprehension of the differentiation process in mesenchymal stem cells.…”
Section: Adipogenesis and Imfmentioning
confidence: 99%
“…SC are multipotent cells capable of transdifferentiating into intramuscular adipocytes when exposed to local cellular signaling (Taylor-Jones et al, 2002;Singh et al, 2007;Lee et al, 2012;Ryan et al, 2013). Moreover, muscle side population (SP) cells are multipotent stem cells that can participate in myogenesis and muscle regeneration upon transplantation (Penton et al, 2013).…”
Section: Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that muscle satellite cells can differentiate into adipocytes following treatments with adipogenic inducers (2,3).…”
Section: Introductionmentioning
confidence: 99%